Strategi Pembelajaran untuk Menerapkan Pedagogik berbasis Teknologi Informasi - Dedy Irfan; Adila Kasni Astiena (JURNAL PTI (PENDIDIKAN DAN TEKNOLOGI INFORMASI) FAKULTAS KEGURUAN ILMU PENDIDIKAN UNIVERSITA PUTRA INDONESIA "YPTK" PADANG, 2022)
Learning in the classroom is the beginning of the learning process carried out by the teacher or lecturer. Subsequent learning can be done directly both in class and outside the classroom. The interactive digital learning process can improve the quality of learning so that it can make it easier for students or students and also make it easier for teachers or lecturers to interact in the learning process. This research was completed by using a descriptive qualitative research type obtained from students who took lectures on Special Teaching Methods or better known as Micro Teaching. The data collection instrument was obtained from a questionnaire from a predetermined sample. Learning with digital processes can be done with information technology-based learning, and technology-based learning can develop conducive and dynamic learning. One of the concepts that can be applied in learning is a learning strategy that is carried out by applying information technology-based pedagogy. To be able to realize conducive and dynamic learning, there are three learning strategies that must be realized: (1) proper and correct pedagogic interpretation by a teacher or lecturer; (2) increasing the collaboration of teachers/lecturers with students/students; (3) the application of information technology in learning.